Pneumocystis jirovecii pneumonia increases the 3-months mortality of anti-MDA5-antibody-positive dermatomyositis patients - Gao, Congcong; Wei, Gaohui; Zhang, Chunyi; Wang, Chenqiong; Li, Chaoying; Li, Ruxu; Su, Zhaohui; Zheng, Zhaohui (Frontiers in Immunology, 2024)
BackgroundAnti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis (anti-MDA5+DM) patients are associated with considerable mortality, and opportunistic infections including Pneumocystis jirovecii pneumonia (PJP)is the main cause. This study was to identify clinical characteristics, risk factors, and prognostic factors of PJP diagnosed by bronchoalveolar lavage fluid (BALF) metagenomic next-generation sequencing (mNGS) in anti-MDA5+ DM patients.MethodsIn this retrospective observational study, all patients admitted with suspected pneumonia were detected for mNGS in BALF. The demographics, comorbidities, laboratory parameters, and treatments of the patients were compared and analyzed in both groups to identify the potential risk factors for PJP and death via Logistic regression and Cox proportional hazards regression, respectively.ResultsOverall, 92 patients were included in this study, 46(50.0%) were defined as PJP+ group, and the other 46 (50.0%) as PJP- group, and 31(67.4%) PJP occurred in the first 3 months. Increased neutrophil-lymphocyte ratio (NLR) and CRP were independent risk factors for PJP occurrence, while trimethoprim-sulfamethoxazole (TMP/SMZ) prophylaxis was an independent protective factor (all p<0.05). The three-months mortality rate was higher in the PJP+ group compared to PJP- group (43.5% vs 23.9%, p=0.047). Rapidly progressive interstitial lung disease (RPILD) was a main predictor of mortality in anti-MDA5+DM patients with PJP, whereas glucocorticoid use was a significant protective factor.ConclusionsPJP has high prevalence and mortality in anti-MDA5+DM, while TMP/SMZ prophylaxis significantly reduces PJP risk. Mortality in PJP+ patients is primarily concentrated within the first 3 months, associated with RPILD. Early intervention with corticosteroids and prophylactic measures are crucial in reducing mortality.